INKUBASI TITONIA PADA TANAH SAWAH TERHADAP ASAM-ASAM ORGANIK - Gusnidar Gusnidar; Nurhajati Hakim; Teguh Budi Prasetyo (Jurnal Solum, 2010)
The research about “Incubation of titonia for organic acid production in rice field”  has been conducted in soil laboratory Agriculture Collage Andalas University Padang, since  January to August 2005.  The objective of this research was to determine the best method of using titonia to produce organic acids in rice field.  The research had 2 factors, 3 series of titonia application and 5 levels of titonia dossages with 3 replications.  The series are: A1 =  Titonia was mixed with soil and then, the soil was directly flooded;  A2 =  Titonia was mixed with soil and then, let them stay on soil surface for 3 weeks before being flooded; A3 = Titonia was mixed with soil and then, the soil was moistened until field capacity for 3 weeks before being flooded.  The second factor was titonia dossages (0,000; 1,250; 2,500; 3,750; 5,000 g  dry weight of titonia per kg soil). The result showed that organic acids of the soil had been changed as a consequence of titonia application and the incubation with soil.  The highest organic acid production was found  at combination of titonia incubation with soil at field capacity for 3 weeks, that was malat acid (184-489 mgl-1). The others detected were citrate, tartarate, malate, and benzoat acids, butt fenolate acids was not detected.  Keywords: incubation, organic acids, rice field, titonia.